Diagnóstico de los portadores energéticos utilizados en “Talleres Maldonado” ubicado en la ciudad de Quito en el año 2015. Diseño de un programa de Producción Más Limpia (PML) para el proceso de enderezada y pintura. - Maldonado Dávila, Carlos Iván (2017)
The purpose of thisstudy was to identify the sources of energy and residual resources that make "Talleres Maldonado" inefficient and less competitive in its market. A diagnosis was made of the energy carriers used in "Talleres Maldonado"; specifically, in the process of straightening and painting. When finding the main problem, viable technical, economic and environmental solutions were formulated to allow the company to maintain a strict control of the carriers; focused on a cleaner Production Plan.